Diagnosing Elementary School Students' Representation of Light Concept Through the Five-tier Diagnostic Test - Adi, Yogi Kuncoro; Widodo, Ari; Sopandi, Wahyu; Muslim (Universitas Pendidikan Ganesha, 2024)
Elementary school students do not yet have a scientific understanding of light. For example, they represent vision as the process of objects being hit by light and the eye being automatically able to see them. Their verbal and visual representations present irrelevance to scientific beliefs. Students need to understand science more comprehensively through multiple-representation learning. The relevant diagnostic tests are needed to find out student multiple-representation profiles. However, diagnostic tests identifying multiple-representation profiles of elementary school students are still rare. This paper aims to communicate the results of development, validity, and reliability, as well as trials of the five-tier diagnostic test (5TDT) in measuring multiple representations of elementary school students about light concepts. The 5TDT is a developed version of the four-tier where there are answer choices and reasons and the level of student confidence in answering both. A package of 15 questions was developed, tested for readability by elementary school teachers and students, and then piloted. Two hundred twenty-seven elementary school students who had studied the concept of light attempted this test. Internal validity was submitted to five experts and showed valid results with several improvement notes. Meanwhile, the results of statistical tests on external validity and reliability show that the five-tier diagnostic test is valid and reliable. The five-tier diagnostic test can measure the diversity of students' representation of their ideas regarding the light concept with more precision. It is shown that they are dominating the Lack of Representation (LOR) level of 39% and Misconception (MIS) level of 31%.